2021
DOI: 10.1111/jac.12487
|View full text |Cite
|
Sign up to set email alerts
|

Trait characterization of genetic resources reveals useful variation for the improvement of cultivated Nordic red clover

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…The present study revealed that cultivated red clover showed a greater tendency to cluster together with wild populations found in the warmer climates of the south and central parts of the Nordic Region with low levels of variation in precipitation and temperature and little to no snow cover. One of the main causes of red clover senescence is repeated freezing and thawing ( Smith, 1957 ; Zanotto et al., 2021 ). However, such information is difficult to model.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that cultivated red clover showed a greater tendency to cluster together with wild populations found in the warmer climates of the south and central parts of the Nordic Region with low levels of variation in precipitation and temperature and little to no snow cover. One of the main causes of red clover senescence is repeated freezing and thawing ( Smith, 1957 ; Zanotto et al., 2021 ). However, such information is difficult to model.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have investigated the variability and inheritance of specific traits such as disease resistance (Frey et al, 2022), seed yield (Herrmann et al, 2005) or flowering time (Jones et al, 2020), only a few studies have investigated phenotypic diversity of several traits within a region or country and even fewer have studied diversity across regions. A study by Zanotto et al (2021) that was conducted with 48 ecotypes and six cultivars from Norway, Sweden, and Finland found large variation in winter survival and yield between the accessions. Wild accessions sometimes outperformed commercial cultivars, indicating their value for improving adaptation to colder climates.…”
Section: Introductionmentioning
confidence: 99%
“…Clover rot, caused by the ascomycete Sclerotinia trifoliorum Eriks., is favored by cooler temperatures, high humidity and long snow cover, and can lead to severe overwintering damage (Saharan and Mehta, 2008). Freezing tolerance is associated with winter survival and is particularly pronounced in wild populations from northern regions (Zanotto et al, 2021). In the warmer climates of Central Europe, persistence is an important breeding target with the specific aim to extend the period of cultivation for red clover cultivars over several growing seasons.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have investigated the variability and inheritance of specific traits such as disease resistance (Frey et al, 2022), seed yield (Herrmann et al, 2005) or flowering time (Jones et al, 2020), only a few studies have investigated phenotypic diversity of several traits within a region or country and even fewer have studied diversity across regions. A study by Zanotto et al (2021) that was conducted with 48 ecotypes and six cultivars from Norway, Sweden, and Finland found large variation in winter survival and yield between red clover accessions. Wild accessions sometimes outperformed commercial cultivars, indicating their value for improving adaptation to colder climates.…”
Section: Introductionmentioning
confidence: 99%